Quantifying the color palettes of Naghsh-e Jahan Square in Isfahan - Mohammadgholipour, Maryam; Kirchner, Eric; Salleh, Elias (John Wiley and Sons Inc., 2020)
In the 1960s, Jean-Philippe Lenclos introduced a structured methodology for determining the color palettes of urban environments. After half a century, this method is widely used all over the world. Since this process contains subjective and time-consuming steps, we propose a quantitative improvement of Lenclos' methodology by introducing a fully digital procedure. This removes observer subjectivity and dependence on local illumination conditions. We applied the digital process to the four monumental buildings of Naghsh-e Jahan Square in Isfahan, a masterpiece of world architecture. The resulting color palettes are more accurate than those obtained in earlier studies. We obtained more accurate color coordinates, characterized by a wider color gamut, and quantified color variations within buildings and between monuments as well